Web Rotational Stiffness of Continuous Steel-Concrete Composite Castellated Beams - Carla Cristiane Silva; Rodrigo Barreto Caldas; Ricardo Hallal Fakury; Hermes Carvalho; João Victor Fragoso Dias (Fracture and Structural Integrity)
Continuous composite beams may suffer a global instability know as lateral distortional buckling (LDB). The design code EN 1994-1-1:2004 provides a procedure for the verification of this ultimate limit state, in which the resistant bending moment to LDB is calculated considering the behavior of the inverted “U-frame” mechanism. An essential parameter for the determination of this moment is the rotational stiffness of the composite beam, which depends on the web stiffness. The EN 1994-1-1:2004 procedure is restricted to composite beams with solid-web steel sections without openings. This paper presents several numerical analyses of the web rotational stiffness of castellated sections such as Anglo-saxon, Litzka and Peiner typology. Finally, based on numerical results obtained, a calculation procedure for determination of this stiffness was proposed.